PEMBERDAYAAN MASYARAKAT PETANI DALAM SWADAYA PUPUK KOMPOS BERBASIS KKN PPM - -, Mutaqin -; Trimaryadi, Totok Heru; -, Triatmanto - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
Community development learning activities for lecturer and students is a medium to contribute to the settlement of the problems in society. The purpose of this proram is: First, to be able to empower farming communities through a community initiative compost manure management to be used as organic compost. Second, introducing appropriate technology composter for the farmers as a tool for the process of making compost from cow manure into organic fertilizer that is efficient and profitable. The method is applied in the framework of empowerment of the target group through observation, interviews, documentation, education, training, practice, coaching, and monitoring of programs. To be in the implementation of these activities can work well, before the student falls on the ground, first given a briefing on the program material that will apply to the target group . The results of the activities of this program are: (1) society has been able to target the group of self-sufficient through the compost cow manure management used as organic compost; (2) the target group has to know, can use and take advantage of appropriate technology in the composter composting process cow manure into organic fertilizer more efficiently and profitably. The implications of this program can serve as a model of community empowerment in a self-sufficient farm compost compost to meet internal needs, and can even be used as a productive economic activity. Keywords: community development, farming community, ability provide compost, animal waste